Proteus mirabilis and Klebsiella pneumoniae as pathogens capable of causing co-infections and exhibiting similarities in their virulence factors - Palusiak, Agata (Frontiers in Cellular and Infection Microbiology, 2022)
The genera Klebsiella and Proteus were independently described in 1885. These Gram-negative rods colonize the human intestinal tract regarded as the main reservoir of these opportunistic pathogens. In favorable conditions they cause infections, often hospital-acquired ones. The activity of K. pneumoniae and P. mirabilis, the leading pathogens within each genus, results in infections of the urinary (UTIs) and respiratory tracts, wounds, bacteremia, affecting mainly immunocompromised patients. P. mirabilis and K. pneumoniae cause polymicrobial UTIs, which are often persistent due to the catheter biofilm formation or increasing resistance of the bacteria to antibiotics. In this situation a need arises to find the antigens with features common to both species. Among many virulence factors produced by both pathogens urease shows some structural similarities but the biggest similarities have been observed in lipids A and the core regions of lipopolysaccharides (LPSs). Both species produce capsular polysaccharides (CPSs) but only in K. pneumoniae these antigens play a crucial role in the serological classification scheme, which in Proteus spp. is based on the structural and serological diversity of LPS O-polysaccharides (OPSs). Structural and serological similarities observed for Klebsiella spp. and Proteus spp. polysaccharides are important in the search for the cross-reacting vaccine antigens.